Medial Femoral Condyle Flap Reconstruction of a Maxillary Defect with a 3D Printing Template - Taylor, Erin M.; Wu, Winona W.; Kamali, Parisa; Ferraro, Nalton; Upton, Joseph; Lin, Samuel J.; Iorio, Matthew L. (Journal of Reconstructive Microsurgery Open, 2017)
Background The medial femoral condyle (MFC) flap is a well-vascularized corticocancellous flap based off the descending genicular artery that can be used to reconstruct difficult bony nonunions. Although frequently used in reconstruction of extremity defects, the MFC flap is rarely used in maxillofacial reconstruction.Methods We present a case example of an MFC vascularized corticocancellous free flap for reconstruction of an ameloblastoma maxillary defect. Additionally, we describe our use of a three-dimensional (3D) template to create an intraoperative osteotomy model for contouring the MFC flap.Results Preoperative 3D printing of the maxillary defect and design of a methylmethacrylate template enabled the precise and rapid contouring of a well-vascularized bone flap. Postoperative 3D CT scan demonstrated satisfactory positioning of the MFC flap within the maxilla.Conclusion The 3D printing technology continues to advance craniofacial reconstruction and allows for the efficient and precise creation of vascularized bone flaps. The MFC vascularized flap has the potential of becoming a workhorse flap in maxillary defect reconstruction alongside the use of 3D printing technology.
Keywords: 3D printing; medial femoral condyle flap; maxillary reconstruction